Lupus pernio without systemic involvement - Gopikrishnan Anjaneyan; Rita Vora (Wolters Kluwer Medknow Publications, 2013)
Sarcoidosis is a multisystem, granulomatous disease of unknown etiology that can affect the pulmonary, reticulo-endothelial, skin, gastrointestinal, cardiac, musculo - skeletal, endocrine or central nervous system. Exclusive cutaneous involvement is very rare in sarcoidosis. Lupus pernio is a variant of cutaneous sarcoidosis presenting with erythematous to violaceous nodules and plaques located symmetrically over the nose, cheeks, ears and digits. We present a case of lupus pernio which showed rapid improvement with topical steroids and has yet not developed any systemic involvement even after 6 years of regular follow up.